Prevalence, attitude and practice of self-medication among adolescents and the paradigm of dysmenorrhea self-care management in different countries - De Sanctis, Vincenzo; Soliman, Ashraf T; Daar, Shahina; Di Maio , Salvatore; Elalaily, Rania; Fiscina, Bernadette; Kattamis, Christos (Acta Biomedica Atenei Parmensis, 2020)
Self-medication (SM) is an important worldwide public health issue affecting children and adolescents. The pattern of SM varies in different communities, affected by factors such as age, sex, income, expense, self-care orientation, educational level and medical knowledge. It is a fairly common practice: for minor health problems, it often provides cheap, rapid, and convenient solutions, outside of the health care system of many countries. Painkillers, antipyretics, cough medicines, cold preparations, dermatological products, nutritional supplements and antibiotics are the drugs most frequently used. Potential risks include incorrect self-diagnosis, improper dosage, inappropriate choice of therapy, masking of severe disease and drug interactions. Lack of awareness of warnings and precautions, storage conditions, the recommended shelf-life and adverse reactions increase the risk of side effects. Little is known about the SM of dysmenorrhea by adolescent girls. Attitudes towards treatment are influenced by cultural, ethnic, and religious factors. Some girls discuss dysmenorrhea with family and friends, and the majority may not seek medical advice. As dysmenorrhea is a common problem for adolescents, it is essential that these girls be aware of the normal and abnormal symptoms of menstruation. In the light of these findings, the roles of family, school, health professionals and health authorities are of utmost importance for the implementation of measures to approach this health problem in a more efficient way.